RESPON HASIL TANAMAN PAPRIKA UNGU TERHADAP PEMBERIAN POC BIO-3 - Eko H A Juwaningsih; Ch. Br Pandaitan; L. Walunguru; N. L. P. R. Cakswindryandani (JURNAL AGRISA, 2023)
Purple pepper is a type of fruiting vegetable plant that has not been widely cultivated in NTT. This plant has high economic value. But its cultivation requires the availability of sufficient nutrients. One of them is Bio-3 liquid organic fertilizer.This study aims to determine the real effect of giving several concentrations of POC Bio-3 on the growth and yield of peppers and the concentration of POC Bio-3 that has a good effect on the growth and yield of peppers. This study used a single-factor group randomized design (RAK) consisting of nine treatments and three repeats, so that there were 27 experimental units. The parameters studied are flower age, fruit age, leaf chlorophyll, plant height, stem diameter, number of productive branches, number of fruits per plant, fruit length, fruit diameter, fruit weight, and fruit weight per plant. The results showed that POC Bio-3 liquid organic fertilizer had a very real influence on the number of fruits per plant, fruit length, fruit diameter, weight per fruit, and fruit weight per plant. POC Bio-3 concentration treatment of 150 ml/l gave the best results on the number of fruits per plant, namely (6.17 pieces); fruit diameter, i.e., (10.54 cm); fruit length (17.20 cm); fruit weight per plant (329.32 g); and POC Bio-3 concentration treatment of 150 ml/l gave the best results on weight per fruit (33.19 g).